PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH PADA PT . BANK SYARIAH MANDIRI KCP PANAM DI PEKANBARU - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The study was conducted at PT. Bank Syariah Mandiri KCP Panam in Pekanbaru. Based on the research background mentioned above, the writer can formulate the problem in this research is Bagaiamanakah pengaru h Loyalty Customer Relationship Marketing at PT. Bank Syariah Mandiri KCP Panam in Pekanbaru .. The purpose of this research was to determine the effect of Loyalty Customer Relationship Marketing at PT. Bank Syariah Mandiri KCP Panam in Pekanbaru. The data analysis in this research by using descriptive and quantitative methods. Methods descriptive analysis of data by the decomposition of the theories contained in the bibliography, and are associated with the data obtained from the research that will be collected, classified and tabulated then be concluded. And quantitative methods with simple linear regression techniques.Samples taken in this study was of 100 people, the research results are seen from the calculation that the value t count was 11 526 and for t_tabel value can be determined by the following formula: t_tabel (? / 2; n-2). Then it can be determined the value t_tabel (0.05 / 2) (100-2). Retrieved t_tabel value of 1.9844 based on the value t_tabel, it can be concluded that the value t count> t table (11 526> 1.9844) H0 is rejected it means a significant difference between Relationship Marketing on customer loyalty, and R Square obtained figures for 0575 show that 57.5% influence of independent variables (Relationship Marketing) on the dependent variable (customer loyalty) while the remaining 42.5% is influenced by other variables not included in this study